Dzierganie wierszy. Salonowe błahostki czy bunt poetki? – na marginesie trzech utworów Gabrieli Puzyniny (1815–1869) - Berkan-Jabłońska, Maria (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
The article presents three little-known poems of the Lithuanian poet and diarist of the first half of the nineteenth century, Gabriela Puzynina. The seemingly trivial subject related to knitting needlework and conventional form of the poems gain a new value, if considered in the context of sociology and anthropology literature. The analysis, beyond the traditional genre study, are subject to the following issues: the poet as a distinct entity and her membership to women’s environment, the process of building the women’s identity, everyday life and its literary reflection, material culture in the comparison with the anthropocentric approach of the past. There is also raised a question about the way of reception such an occasional literature today. According to the author of the article, reading Puzynina’s poems only as “the literary trifles” wrongfully condemned them to oblivion, yet they are interesting and credible testimony of historical time and a medium for exploring the individual human life from the past.